The finding of black currants from sect. Eucoreosma (Grossulariaceae) in the central part of southern Primorsky Territory, Russia - L. A. Fedina; M. A. Polezhaeva; D. R. Iunusova; M. N. Koldaeva; A. Sh. Sabitov (Труды по прикладной ботанике, генетике и селекции)
Background. The ever increasing anthropogenic impact on natural populations of rare and, especially, endangered plant species has recently become even more forceful. Therefore, the finding of a small black currant population representing sect. Eucoreosma (Spach) Jancz. within a natural environment in the south of Primorsky Territory appears highly important. Previously, none of the black currant species was recorded as occurring in this area. Materials and methods. Plants from the new locality were compared with accessions of Ribes nigrum L., R. ussuriense Jancz., R. pauciflorum Turcz. ex Pojark., and R. fontaneum Boczkarn. using morphological and molecular genetics techniques. Results and conclusion. A molecular genetics analysis of two chloroplast DNA fragments excluded any association of the discovered plants with R. nigrum or R. fontaneum. Meanwhile, no differences in chloroplast DNA fragments were found between these plants and R. ussuriense and R. pauciflorum accessions. A number of morphological features attested to a possibility to attribute the finding to the rare species R. ussuriense: its isolated localities had previously been reported in southern Primorsky Territory. The differences in chloroplast DNA fragments between the Siberian/Far Eastern species R. pauciflorum and the European/Siberian species R. nigrum make doubtful their possible fusion, based only on morphological characters, and require further studies.